2004
DOI: 10.17986/blm.200493554
|View full text |Cite
|
Sign up to set email alerts
|

Adana’da Trafik Kazalarına Bağlı Ölümlerin Değerlendirilmesi

Abstract: …ZET SUMMARYTraffic accidents play important role in the daily routine of forensic practices. Thousands of people die or get injured due to traffic accidents each year. Traffic accidents and the data must be very well over viewed and analyzed for to assure correct protective and preventive safeties.In this study we have analyzed the data of the Adana District Attorney, the Legal Medicine Branch and Morgue Unit of the Adana Branch of the Turkish Forensic Medicine Council between the dates 01.01. 2001-31.12.2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
7
Order By: Relevance
“…In the present study, head trauma (40.4%) was the second leading cause of death after whole body trauma (44.3%). This rate has been reported to be 59.1% in the study by Gören et al, [13] 83.3% in the study by Karbeyaz et al, [14] and 61.5% in the study conducted by Hilal et al [18] In a study evaluating the cases presented to emergency rooms after traffic accidents in the province of Sivas, Turkey, head trauma has been detected in 18.6% of the cases. [38] Çırak et al [39] have reported traffic accidents as the cause in 48% of head trauma cases presented to the emergency room.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the present study, head trauma (40.4%) was the second leading cause of death after whole body trauma (44.3%). This rate has been reported to be 59.1% in the study by Gören et al, [13] 83.3% in the study by Karbeyaz et al, [14] and 61.5% in the study conducted by Hilal et al [18] In a study evaluating the cases presented to emergency rooms after traffic accidents in the province of Sivas, Turkey, head trauma has been detected in 18.6% of the cases. [38] Çırak et al [39] have reported traffic accidents as the cause in 48% of head trauma cases presented to the emergency room.…”
Section: Discussionmentioning
confidence: 95%
“…[17] The present study comprised 281 (84.1%) male cases and 53 (15.9%) female cases with a male to female ratio of 5.3, which was consistent with the findings reported in the relevant studies. [13,[18][19][20][21][22][23][24][25][26] This was attributed to the higher male count in traffic. Studies conducted in Turkey have reported that the cases involved in traffic accidents are predominantly in the young age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çocukluk çağındaki trafik kazasına bağlı ölüm-lerin daha çok sokakta oynayan (yaya veya bisikletli) çocuklarda görülmesi, sıklıkla anne ve babasının koruma ve gözetiminde olması gereken çocukların sokakta korumasız, tedbirsiz kendi başlarına bırakılması ve kendini tehlikelerden koruyamaması ile ilişkilendirilmiştir. Dünyada olduğu gibi ülkemiz açısından da büyük bir halk sağlığı problemi olan trafik kazalarının önlen-mesi için alınabilecek çeşitli önlemler içerisinde, yaya ve sürücülerin eğitimi, yol ve araçların trafik için uygunluğunun sağlanması, güvenlik önlem-lerinin eksiksiz uygulanması sayılmaktadır (21). Ev kazaları ve çevresel kazalar nedeniyle çocuk ölümleri Dünya çapında önemli bir halk sağlığı sorunu olup özellikle Türkiye gibi gelişmekte olan ülkelerin, yanı sıra az gelişmiş ülkelerde olduğu gibi, tüm kazalardan çocukların korunması amaçlanmalıdır.…”
Section: Discussionunclassified
“…Çal›flmada ölen 21 olgudan sadece 2 (%9.5) olguya klasik otopsi yap›lm›flt›r. Trafik kazas› sonucu ölen olgulara otopsi yap›lma oran› Adana'da yap›lan bir çal›flmada %6.9 olarak bildirilmifltir (38). Hasta dosyas›ndaki bulgular ile otopsi bulgular›n›n karfl›laflt›r›ld›¤› çal›flmalarda, arada farkl›l›klar olabilece¤i, fizik muayene ve görüntüleme yöntemleriyle tespit edilemeyen bulgular›n otopside ortaya ç›kabilece¤i gösterilmifltir (39).…”
Section: Gereç Ve Yöntemunclassified